Pengaruh Kreativitas ,Inovasi Dan Pengetahuan Kewirausahaan Terhadap Keberhasila Usaha Pada Toko Parfum - Rahma Sonang Ritonga; Ratih Mala; Siti Tri Adha; Hasyim Hasyim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to explore the influence of creativity, innovation and entrepreneurial knowledge on business success in perfume shops. Creativity is needed to generate new ideas, while innovation involves implementing these ideas in the resulting product or service. Apart from that, entrepreneurial knowledge is also needed in managing a business and identifying new opportunities. Through survey methods and statistical analysis, this research shows that there is a positive relationship between creativity, innovation and knowledge entrepreneurship and business success in perfume shops. The implication of this research is the importance of developing creativity, innovation and entrepreneurial knowledge in improving business performance in perfume shops.